Comparative Analysis of Suture Techniques in Emergency Laparotomy for Peritonitis: Continuous Versus Interrupted Suturing in Abdominal Wall Closure for Optimal Wound Healing - Hassan, Syed Shams ul; Mahar, Tania; Nadeem, Asif; Ahmad, Shafiq; Yamin, Kiran; Akhtar, Naveed (Biological and Clinical Sciences Research Journal, 2025)
Wound dehiscence and infection are major postoperative complications following emergency laparotomy, often necessitating secondary wound closure and leading to increased morbidity and higher recurrence rates. This study aimed to compare outcomes (in terms of wound dehiscence and wound infection) with continuous suture technique versus interrupted sutures technique in abdominal wall closure among patients undergoing emergency laparotomy due to peritonitis. Methodology: A total of 156 patients undergoing emergency laparotomy due to peritonitis were included in this study. After selection, these patients were randomly divided into two groups using the draws method. Patients in group A (n = 78) were managed by continuous suture technique (polypropylene #1 suture) whereas in group B, also having 78 patients, closure of rectus sheath was done by interrupted suture technique (1 centimetre apart and away from edges) by same surgeon having more than 10 years experience after post-graduation. Patients were called for follow-up every week for a maximum of 4 weeks to observe wound dehiscence and wound infection and findings were noted in the proforma. Data entry and analysis were done using SPSS–23. Results: Mean age of our study cases was 36.91 ± 9.00 years (range; 22 – 56 years) while 71.2 % (n = 111) were aged up to 40 years. Wound dehiscence was noted in 12.8% of all patients while it was 5.1%(n = 4) in group A compared with 20.5 % (n = 16) in group B. (P = 0.008). Wound infection was noted in 13.5% (n = 21), and in group A, infection was 3.8% (n = 3) compared with 23.1% (n = 18) in group B. (P = 0.001). Conclusion: Our study results indicate that continuous suturing of the rectus sheath in abdominal wall closure in an emergency laparotomy is safe, reliable, and effective as it is associated with significantly less wound dehiscence and infection burden.